2011
DOI: 10.1007/s11130-011-0266-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Sources of Fructans on Body Weight, Blood Metabolites and Fecal Bacteria in Normal and Obese non-diabetic and Diabetic Rats

Abstract: Fructans contribute significantly to dietary fiber with beneficial effects on gastrointestinal physiology in healthy individuals and offer a promising approach to treating some diseases. Two experiments (Experiment 1 = rats with normal weight; Experiment 2 = obese rats) were developed to compare the effects of three fructan sources (Cichorium intybus L. Asteraceae, Helianthus tuberosus L. Asteraceae and Agave angustifolia ssp. tequilana Haw, Agavaceae) on body weight change, blood metabolites and fecal bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…Additional characterization of bacterial crossfeeding via in vitro models and computational simulations will also help advance our understanding of the role of diet on the microbiome. Because rodent studies have provided evidence for the benefits of agave inulin supplementation on body composition, blood cholesterol, and blood glucose concentrations (45)(46)(47), further investigation is warranted to determine whether these effects translate into health benefits in human populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional characterization of bacterial crossfeeding via in vitro models and computational simulations will also help advance our understanding of the role of diet on the microbiome. Because rodent studies have provided evidence for the benefits of agave inulin supplementation on body composition, blood cholesterol, and blood glucose concentrations (45)(46)(47), further investigation is warranted to determine whether these effects translate into health benefits in human populations.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experimentation has demonstrated that agave inulin is readily fermented by bifidobacteria and lactobacilli (43,44). In addition, rodent studies have provided evidence that the botanical origin and chemical structure of different inulin-type fibers (e.g., agave inulin and chicory inulin) induce variable effects on body composition, blood cholesterol, and blood glucose concentrations (45)(46)(47). The prebiotic effects of agave inulin in healthy adults, however, are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the microbial mechanisms remain in unclear [12,13]. New molecular techniques that enable analysis of non-cultivable bacteria are starting to be applied in studies investigating the impact of prebiotics on the cecal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence showed that the physicochemical properties of dietary fiber such as viscosity, water-binding capacity, and fermentability may contribute to decrease the food intake in human beings and rodents [3,4,5]. Viscous fibers increase chewing activity and saliva production in the mouth [6], which could result in early satiation and reduced food intake [7,8].…”
Section: Introductionmentioning
confidence: 99%